2021
DOI: 10.1161/strokeaha.121.034150
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Collateral Damage of the COVID-19 Pandemic on Stroke Care

Abstract: Background and Purpose: During the coronavirus disease 2019 (COVID-19) pandemic, the various emergency measures implemented to contain the spread of the virus and to overcome the volume of affected patients presenting to hospitals may have had unintended consequences. Several studies reported a decrease in the number of stroke admissions. There are no data on the impact of the COVID-19 pandemic on stroke admissions and stroke care in Maryland. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…This may be related to possible delayed hospital arrival and an overall decrease in the absolute number of patients with mild and moderate stroke seeking medical care. 21,29,30,46,54,55,59,60,62,70 However, the likelihood of being treated with IVT did not differ between two periods in comprehensive stroke centers and that of being treated with EVT increased during the pandemic, which might be due to adequate changes made in workflow of acute stroke care in comprehensive stroke centers. 71 Higher likelihood of being treated with EVT might also have been caused by higher likelihood of large vessel occlusions due to prothrombotic state driven by COVID-19 virus, as reported by multiple studies.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This may be related to possible delayed hospital arrival and an overall decrease in the absolute number of patients with mild and moderate stroke seeking medical care. 21,29,30,46,54,55,59,60,62,70 However, the likelihood of being treated with IVT did not differ between two periods in comprehensive stroke centers and that of being treated with EVT increased during the pandemic, which might be due to adequate changes made in workflow of acute stroke care in comprehensive stroke centers. 71 Higher likelihood of being treated with EVT might also have been caused by higher likelihood of large vessel occlusions due to prothrombotic state driven by COVID-19 virus, as reported by multiple studies.…”
Section: Discussionmentioning
confidence: 95%
“…8, Twenty-four studies met criteria for 'good' quality and 13 met criteria for 'fair' quality (Supplemetary Tables 2-4). Most studies compared the pandemic period (ranging from January to June 2020) to a similar period in the preceding year (range January to June 2019) [28][29][30][31]33,35,39,[41][42][43]45,46,[48][49][50]52,[54][55][56][57][58]60 or the months preceding the pandemic (range September 2019 to December 2019). 8,32,34,[36][37][38]40,44,47,51,53,59,[61][62][63]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that delays in surgery among cancer patients impacted their long-term survival, and the proportion of advanced stages of malignancies increased during the pandemic [4]. On the other hand, as the pandemic continues over a long period, there were rising concerns for non-COVID-19 patients requiring urgent care, such as acute coronary syndrome, stroke, or appendicitis [5][6][7][8]. During the national lockdown in Italy, COVID-19 changed the quality of emergent surgical care with poorer prognosis and higher mortality rates [9].…”
Section: Introductionmentioning
confidence: 99%
“…The relationships between SARS-CoV-2 and the dissecting aneurysm that we described in our paper are only hypothetical [2] , as Dr. Finsterer pointed out [1] . There is a report that the number of hospitalizations for acute stroke patients, especially for ischemic stroke ones, declined, resulting in that the number of hospitalizations for aneurysmal SAH patients increased relatively under the COVID-19 pandemic compared with the pre-pandemic period, although the exact reasons are unknown [3] . Dissecting aneurysms differ from saccular aneurysms, and are most common in the East Asian population, particularly in males, and in the vertebrobasilar artery, accounting for only 3−5% of aneurysmal SAH cases in the general population [4] .…”
mentioning
confidence: 99%